Effects of adding mixed chicken and quail egg yolks to the cryodiluent on the quality of ram semen before and after cryopreservation - Swelum, Ayman A.; Ba-Awadh, Hani A.; Olarinre, Isiaka O.; Saadeldin, Islam M.; Alowaimer, Abdullah N. (Frontiers in Veterinary Science, 2022)
The effects of adding mixed chicken and Japanese quail egg yolks (EYs) to the cryodiluent on the quality of ram semen before freezing and post-thawing were evaluated. Additionally, the composition of chicken and quail egg EYs and their mixture were analyzed for results explanation. The semen was collected from rams (n= 5) and extended with cryodiluent containing the EY of chicken, quail or their mixture (1:1). The extended semen was chilled slowly to 5 °C within two hours and equilibrated for two hours, before frozen on the liquid nitrogen vapor and cryopreserved at −196 °C. The straws were evaluated before freezing and post-thawing for sperm motility, vitality and abnormality besides plasma-membrane and DNA integrities. The moisture, ash, protein, and fatty acid (FA) contents of chicken EY, quail EY and their mixture were analyzed. Sperm vitality, plasma membrane integrity and DNA integrity before freezing were significantly (P < 0.05) higher in quail EY than chicken EY and mixed EYs cryodiluent. The chicken EY extender significantly improved the vitality, plasma membrane and DNA integrities of post-thawed ram semen in comparison with quail EY or mixed EYs extenders. While, the post-thawing sperm abnormalities was lower (P≤ 0.05) in quail EY than chicken EY and mixed EYs cryodiluent. The post-thawing sperm motion kinetics parameters were higher in quail EY than chicken EY and mixed EYs cryodiluent. The highest percentages of moisture, ash, saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) were detected in quail EY had. While, the highest percentages of fat, protein and polyunsaturated fatty acids (PUFAs) were detected in chicken EY. In conclusion, using of chicken EY can improve total motility, vitality, plasma membrane integrity and DNA integrity of cryopreserved ram semen. While, using of quail EY can improve sperm abnormalities and kinetic motion parameters of cryopreserved ram semen. Mixing chicken and quail EYs added no value for post-thawing ram semen parameters.